The Effects Of Career Development, Organizational Climate, and Leadership Style on Employee Satisfaction - Yogi Yuli Antoro; Anik Herminingsih (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
Job satisfaction is an important thing in human resource management, because it will affect the positive behaviors of the employees.This study aims to examine and analyze the effect of career development, organizational climate and leadership style on employee job satisfaction. Population in this research is 120 employees of PT. Astra International Tbk. Auto 2000 Puri Kembangan. The sample used is 93 employees, calculated based on the Slovin formula. The Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method using Partial Least Square (PLS). The results of this study indicate that the career development variable has a positive and significant effect on job satisfaction. Organizational climate variable has a positive and significant effect on job satisfaction. And the leadership style variable has a positive and significant effect on job satisfaction.